2011
DOI: 10.4187/respcare.00656
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Support Ventilation Advisory System Provides Valid Recommendations for Setting Ventilator

Abstract: BACKGROUND: Pressure support ventilation (PSV) should be applied so that the inspiratory muscles are unloaded appropriately. We developed a computerized advisory system that assesses the load on the inspiratory muscles to spontaneously inhale, reflected by the automatically and noninvasively measured work of breathing per minute, and tolerance for that load, reflected by spontaneous breathing frequency and tidal volume, in a fuzzy-logic algorithm that provides recommendations for setting PSV. We call this a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…WOB is calculated from the measured V I and the P calculated from the equation of motion: WOB ϭ ͐P ϫ V. Power of breathing (WOB/min) is the rate at which work is done as a measure over time, not for an individual breath. [42][43][44][45][46] This may be a better assessment of respiratory muscle load than WOB/breath. Normal power of breathing is 4 -8 J/min.…”
Section: Work Of Breathingmentioning
confidence: 99%
“…WOB is calculated from the measured V I and the P calculated from the equation of motion: WOB ϭ ͐P ϫ V. Power of breathing (WOB/min) is the rate at which work is done as a measure over time, not for an individual breath. [42][43][44][45][46] This may be a better assessment of respiratory muscle load than WOB/breath. Normal power of breathing is 4 -8 J/min.…”
Section: Work Of Breathingmentioning
confidence: 99%
“…Hepatic vascular resistance is also elevated in mechanically ventilated patients. (23) As regard serum urea level, Patients with elevated urea level were significantly experienced difficult and prolonged weaning in comparison to patients with simple weaning (P= 0.005& 0.004 respectively),these results was in agreement with the result of the study of Yao-Kuang, et al (24) who reported that high blood urea nitrogen (BUN) levels were associated with weaning failure, this can be explained as elevated BUN levels may be indicative of impaired renal function, reduced kidney blood flow and/or excessive protein catabolism resulting in muscle wasting and a negative nitrogen balance.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of RESPIRATORY CARE, Bonnett and colleagues 4 "reintroduce" readers to a computerized system meant to aid in the provision of care to patients requiring mechanical ventilation. They described an open-loop advisory system that continuously provides caregivers recommendations relevant to the titration of pressure support ventilation (PSV).…”
Section: See the Original Study On Page 271mentioning
confidence: 99%